SOME RESULTS OF REALIZATION OF THE PROGRAM ON DEVELOPMENT OF THE ACTIVITIES OF STUDENT UNIONS - Raisa M. Petruneva; Valentina D. Vasil'Eva (Moscow Polytechnic University, 2016)
The key theme of the article is the role of student youth in social development. In 2012 the Ministry of Education and Science of Russia has initiated the Program on development of the activities of student unions. The article analyzes the outcomes of 2012- 2013 of the Program realization at Volgograd State Technical University.